Controlling Ferromagnetic Ground States and Solitons in Thin Films and Nanowires Built from Iron Phthalocyanine Chains. (27th May 2019) - Wu, Zhenlin; Robaschik, Peter; Fleet, Luke R.; Felton, Solveig; Aeppli, Gabriel; Heutz, Sandrine
Abstract: Iron phthalocyanine (FePc) is a molecular semiconductor whose building blocks are 1D ferromagnetic chains. It is shown that its optical and magnetic properties are controlled by the growth strategy, obtaining extremely high coercivities of over 1 T and modulating the exchange constant between 15 and 29 K through switching from thin films with controlled orientations, to ultralong nanowires. Magnetization measurements are analyzed using concepts and formulas with broad applicability to all 1D ferromagnetic chains. They show that FePc is best described by a xy model with moments preferentially lying in the molecular planes. The chain Hamiltonian is very similar to that for the classic inorganic magnet CsNiF3, but with ferromagnetic rather than antiferromagnetic interchain interactions. The dominant degrees of freedom are topological excitations called solitons, namely moving 1D magnetic domain walls, and at low temperatures and fields a "super‐Curie–Weiss" law characteristic of nearly 1D xy and Heisenberg ferromagnets, where susceptibility scales as 1/( T 2 –θ 2 ), is observed. The ability to control the molecular orientation and ferromagnetism of FePc systems, and produce them on flexible substrates, together with excellent transistor characteristics reported previously for phthalocyanine analogues, makes them potentially useful for magneto‐optical and spintronic devices. Abstract : Ferromagnetic films and nanowires of the molecular semiconductor iron phthalocyanine are fabricated on flexible substrates. By controlling the molecular orientation, crystal structure, and crystal size, ferromagnetic couplings of 20–28 K are obtained, with record coercivities of 1T achieved in nanowires. The dominant degrees of freedom in these 1D magnetic semiconductors are solitons, topologically stable twists in magnetization.